Death in Venice [videorecording (DVD)] - Visconti, Luchino, 1906-1976; Bogarde, Dirk, 1921-1999; Andresen, Björn, 1955-; Valli, Romolo, 1925-1980; Berenson, Marisa, 1942-; Mann, Thomas, 1875-1955 (Criterion collection, 2019)
A fastidious composer reeling from a disastrous concert, Gustav von Aschenbach (Dirk Bogarde) travels to Venice to recover. There, he is struck by a vision of pure beauty in the form of a young boy named Tadzio (Björn Andrésen), his infatuation developing into an obsession even as rumors of a plague spread through the city. Based on the novella by Thomas Mann, this late masterpiece from Luchino Visconti is a meditation on the nature of art, the allure of beauty, and the inescapability of death. Setting Mann's story of queer desire and bodily decay against the music of Gustav Mahler, it is one of cinema's most exalted literary adaptations.